2020
DOI: 10.1007/s11096-020-01134-w
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of patients’ knowledge about oral anticoagulant medicines and use of alert cards by community pharmacists

Abstract: Background Anticoagulants continue to pose high risk of harm to patients despite the discovery of novel direct-acting oral anticoagulant agents that require less monitoring than warfarin. Objective To evaluate patients’ knowledge about their oral anticoagulants and the potential role for community pharmacists in optimising safety. Setting Community pharmacies in England. Methods An online survey-based evaluation conducted over a 5-month period to ascertain patients’ knowledge, use of anticoagulant alert cards,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…99 Educating patients about the importance of taking inhaled therapies as prescribed, good inhaler technique and the risks associated with SCS may encourage patients to favour medications with less risk of adverse outcomes than SCS. If SCS therapy is required, it is important that patients are aware of the risks, which could be presented in the form of a reference card (similar to anticoagulant alert cards used by patients treated with warfarin) 100 that provides key information such as common adverse events and SCS dosing limits and could also be used to document SCS exposure levels over time. Educating patients on how to more effectively self-assess asthma severity and control would also help to match the proper treatment approach to the patient's current need.…”
Section: Education and Raising Awarenessmentioning
confidence: 99%
“…99 Educating patients about the importance of taking inhaled therapies as prescribed, good inhaler technique and the risks associated with SCS may encourage patients to favour medications with less risk of adverse outcomes than SCS. If SCS therapy is required, it is important that patients are aware of the risks, which could be presented in the form of a reference card (similar to anticoagulant alert cards used by patients treated with warfarin) 100 that provides key information such as common adverse events and SCS dosing limits and could also be used to document SCS exposure levels over time. Educating patients on how to more effectively self-assess asthma severity and control would also help to match the proper treatment approach to the patient's current need.…”
Section: Education and Raising Awarenessmentioning
confidence: 99%
“…Research 3 has shown that pharmacists can successfully intervene when a medicine is newly prescribed, with repeated follow up in the short term, to increase effective medicine taking for the treatment of a long-term condition. The NMS significantly increased the proportion of patients adhering to their new medicine by about 10%, 4 compared with normal practice.…”
Section: Rationalementioning
confidence: 99%
“…In the 2017-18 audit, 11% of patients received their anticoagulant medicine in an MDS compliance aid. 3 For DOACs, dabigatran is the only agent where the manufacturer advises that it should be left in the original foil wrapping (i.e. not repackaged) to protect from moisture and it is important that pharmacies are aware of this.…”
Section: Patient Alert Cardsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be explained by departmental prioritization of optimizing medications before discharge and relying on our well-positioned community pharmacy colleagues to provide education once patients' medication therapy has been optimized. 11,12 The Canadian Cardiovascular Society Atrial Fibrillation Guidelines 2010 recommended a transition in practice from warfarin to direct oral anticoagulants (DOACs) as preferred first-line therapy, 13 which may have affected pharmacists' anticoagulant interventions during the study period. However, given that the AIM High system was implemented in 2015 and DOACs have been the standard of care in Regina (according to the anticoagulant clinical practice standard) since 2014, the effect of the 2010 guidelines on local data is thought to be minimal.…”
mentioning
confidence: 99%